Social media and social behavior of adolescents in Puseurjaya, Karawang - Ramadhani, Kholisul Irfan; Banowati, Eva; Handoyo, Eko (Universitas Negeri Semarang, 2024)
Nowadays, adolescents are facilitated by the means applied through practical knowledge of the method, rationally leading to efficiency in the application of adolescent life. We can say that adolescents today are influenced by technology. This article's goal is to clarify the reasons why adolescents in Puseurjaya Village are interested in using social media, especially Tiktok, in their daily lives. Furthermore, the author has a hope that this article will provide sufficient knowledge in the field of social media, especially for adolescents and their parents, to support their education. This research uses a descriptive-qualitative approach, which means searching for facts, researching social issues, and specific circumstances, such as relationships and activities, that exist in the nomena world, the invisible world, or the human senses, as well as affect his life. In conclusion, adolescents in Puseurjaya Village are interested in using social media, especially Tiktok, based on following their friends and current trends. Overall, the support and supervision provided by parents regarding adolescent use of social media has a positive impact on maintaining their mental health, manners, and physical health. Through open communication, guidance, and attention, parents can help adolescents develop healthy and responsible behavioural patterns in the digital world.